Influence of N-introduction on the electronic structure and properties of polyacenes: experiment and quantum chemistry in concert - Dreuw, Andreas; Tegeder, Petra (Physical chemistry, chemical physics, 2023)
N-Heteropolycycles (NHPCs) represent a promising substance class for applications in functional organic materials, since their electronic structure and the resulting individual molecular properties are efficiently tuneable by number and position of nitrogen atoms in the aromatic structural backbone. The isosteric replacement of a C-H unit by N leaves the geometric structure unchanged, while ionization potential, electron affinity and absorption spectra are altered. In this prespective, we present the potent combination of two-photon photoelectron spectroscopy (2PPE) and high-resolution electron energy loss spectroscopy (HREELS) with quantum chemical calculations for the investigation of the electronic structure of NHCPs. In contrast to conventional optical spectroscopies, 2PPE provides insight into electron-detached and attached electronic states of NHCPs, while HREELS delivers the energetic position of the lowest triplet states. Based on our comprehensive investigations, an extension of Platt's famous nomenclature of the low-lying excited ππ* states could be suggested for NHPCs based on the physical properties of the corresponding excitons. Also, the influence of N-introduction onto the occurrence of the so-called α-band in NHPCs compared to the parent polycyclic aromatic hydrocarbons could be explained in detail. While N-substitution of C-H in polycyclic aromatic hydrocarbons (PAHs) is often seen as a simple isosteric replacement, it has a strong influence on the electronic structure and the resulting properties. Therefore rules derived for PAHs can often only be transferred to a limited extent or not at all.
Gesehen am 16.04.2024